Kadro dergisi üzerinden bir deneme: " Milli iktisat'tan devletçiliğe" - (:unkn) unknown (My University, 2012)
Cumhuriyetin kurulması ile beraber iktisadi düşüncede değişiklik olmamış, milli iktisat düşüncesi ekonomi politikalarında belirleyici olmaya devam etmiştir. 1930’lardan sonra ise milli iktisat politikalarının odak noktası olan milli tüccar hedefi yerini ulus-devlet ekonomisine bırakmıştır. Bu çalışma ile Cumhuriyet dönemi ekonomi politikaları ile Cumhuriyet öncesi milli iktisat politikaları arasında süreklilik bulunduğu ve devletçilik politikalarının milli iktisat politikalarının devamı niteliğinde olduğunun vurgulanması amaçlanmıştır. Bu amacın, Türkiye ekonomi ve siyasi literatüründe bir yeri olan Kadro Dergisi’nden yararlanarak gerçekleştirilebileceği görülmüştür. Bu nedenle yakın iktisat tarihimiz ekonomi politikalarında yer alan milli iktisat ve devletçilik kavramlarının Kadro Dergisi’nde bu konuda öne çıkan yazılar doğrultusunda ele alınması denenmiştir. Kadro Dergisi yazarlarından meydana gelen Kadro Hareketi, resmi otoritelerce yeterince tanımlanmayan devletçilik ilkesini açık bir şekilde tanımlamış ve milli iktisat politikalarının devamı niteliğindeki görüşlerini savunmuştur. Keşifsel bir yöntemle yazılan bu makale devletçilik uygulamalarının milli iktisattan ulus devlete giden sürecin aslında sonucu olduğu savını da tartışmaya açmayı denemektedir. Böylece Cumhuriyet dönemi iktisat tarihine ilişkin çalışmaların ve yapılan dönemlendirmelerin, yeni varsayımlarla sorgulanması ve yeniden değerlendirilmesi amaçlanmıştır.-

With the establishment of the Turkish Republic, the economic thought did not undergo any significant change, as the idea of National Economics maintained its decisive role in the economic policy of Turkey. This study aims at underlining the continuity between the economic policies during the Republican era and pre-Republican national economic policies, and highlighting the fact that statist policies were actually a continuation of national economic policies. The present study aims to underline the continuity between the economic policies during the Republican era and pre-Republican national economic policies, and to highlight the fact that statist policies were actually a continuation of national economic policies. Enjoying a prominent place in the relevant literature, the famous “Kadro Journal” of the period is indeed a useful tool to such an end. Thus, through the perspective of the prominent articles published in Kadro Journal, the study attempts to present a discussion on the concepts of national economics and statism, which played an important role in the economic policies of the near history of Turkey. Through the columnists of the Kadro Journal, the Kadro Movement defined the principle of statism and advocated the ideas which were a continuation of national economic policies. This article written in an exploratory method also attempts to call into question the claim that statist economic practices were actually the result of a transition process from national economics to nation-state. It also aims at questioning and revising, on the basis of new assumptions, the studies as well as periodization attempts pertaining to the economic history of Republican Turkey.
An essay on"Transition from national economics ( Milli İktisat ) to statism "Based upon Kadro journal